2020
DOI: 10.5194/tc-14-2409-2020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical predictability of the Arctic sea ice volume anomaly: identifying predictors and optimal sampling locations

Abstract: Abstract. This work evaluates the statistical predictability of the Arctic sea ice volume (SIV) anomaly – here defined as the detrended and deseasonalized SIV – on the interannual timescale. To do so, we made use of six datasets, from three different atmosphere–ocean general circulation models, with two different horizontal grid resolutions each. Based on these datasets, we have developed a statistical empirical model which in turn was used to test the performance of different predictor variables, as well as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Figure 3a, b show the mean Arctic sea ice circulation over the pre-industrial period by compositing the low (a) and high (b) indices for the first mode of SIT variability. The sea ice drift anomaly associated with the pos-itive and negative phases of the first SIT mode shares similar features with the Arctic Oscillation: a cyclonic anomaly in the Beaufort Gyre, impacting the Transpolar Drift Stream, the Laptev Sea Gyre and the East Siberian circulation, as described by Rigor et al (2002). Furthermore, applying wavelet analysis to the associated time series of the first spatial mode of variability indicates that the main periodicity of this mode is centred on 8 years and spans from 5 to 10 years (not shown).…”
Section: Drivers Of the Major Modes Of Sit Internal Variabilitymentioning
confidence: 70%
See 1 more Smart Citation
“…Figure 3a, b show the mean Arctic sea ice circulation over the pre-industrial period by compositing the low (a) and high (b) indices for the first mode of SIT variability. The sea ice drift anomaly associated with the pos-itive and negative phases of the first SIT mode shares similar features with the Arctic Oscillation: a cyclonic anomaly in the Beaufort Gyre, impacting the Transpolar Drift Stream, the Laptev Sea Gyre and the East Siberian circulation, as described by Rigor et al (2002). Furthermore, applying wavelet analysis to the associated time series of the first spatial mode of variability indicates that the main periodicity of this mode is centred on 8 years and spans from 5 to 10 years (not shown).…”
Section: Drivers Of the Major Modes Of Sit Internal Variabilitymentioning
confidence: 70%
“…However, to validate and improve our predictions, observational data are crucial. In this sense, our variability analysis of internal SIV and SIT variability might help the development of an optimal sampling strategy, taking into account the selection of well-placed sampling locations for monitoring the SIT and, therefore, the pan-Arctic SIV that are not as well documented as the sea ice extent and area (Ponsoni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cross-disciplinary integration, many cryosphere studies have a history of international collaborations not only across traditional disciplines but also across spatial and/or temporal scales (I-integrated). For example, the recent Year of Polar Prediction (YOPP) and the European Union Horizon 2020 project APPLICATE brought together the efforts from several international partners to, among other goals, improve the prediction capability of polar regions including their cryosphere components (sea ice and snow), from weather to climate scales (Jung et al, 2016), by making better use of observational (in situ and satellite) data sets and model outputs (C-coordinated) (Ponsoni et al, 2020). Furthermore, the YOPP-endorsed activities are making data openly accessible (O-open).…”
Section: Observational and Modeling Data Research And Application In ...mentioning
confidence: 99%
“…This finding suggests that a limited number of well-placed in situ monitoring stations could be sufficient to estimate the large-scale changes in sea-ice thickness and volume on interannual time-scales (Ponsoni et al, 2020), especially if the in situ data records are complemented and cross-validated by large-scale satellite retrievals, for which large uncertainties remain (Zygmuntowska et al, 2014). A proposed list of 10 sampling sites is given in Ponsoni et al (2020) and is illustrated in Figure 1 (middle panel). According to their study, sea-ice thickness measurements sampled from as little as six well-placed stations are sufficient to reconstruct most (80%) of the actual sea-ice volume variability.…”
Section: Defining Strategies For Monitoring Arctic Sea-ice Volume Variabilitymentioning
confidence: 99%
“…An analysis of the simulated sea-ice thicknesses in state-of-the-art climate models participating in the High Resolution Model Intercomparison Project (High-ResMIP: Haarsma et al, 2016) of CMIP6 has revealed that the variability of this field exhibits significant spatial auto-correlation if grid-cell averages and monthly means are considered. This finding suggests that a limited number of well-placed in situ monitoring stations could be sufficient to estimate the large-scale changes in sea-ice thickness and volume on interannual time-scales (Ponsoni et al, 2020), especially if the in situ data records are complemented and cross-validated by large-scale satellite retrievals, for which large uncertainties remain (Zygmuntowska et al, 2014). A proposed list of 10 sampling sites is given in Ponsoni et al (2020) and is illustrated in Figure 1 (middle panel).…”
Section: Defining Strategies For Monitoring Arctic Sea-ice Volume Var...mentioning
confidence: 99%